2008
DOI: 10.1098/rsbl.2008.0528
|View full text |Cite
|
Sign up to set email alerts
|

Mating behaviour inLymnaea stagnalispond snails is a maternally inherited, lateralized trait

Abstract: Lateralization of the brain has traditionally been considered a specialization that is confined to the vertebrates, but recent studies have revealed that a range of invertebrates also have a brain that is structurally asymmetric and/or each side performs a different set of functions. Here, we show that the precopulatory mating behaviour of the pond snail Lymnaea stagnalis is lateralized. We present evidence that the asymmetry of the behaviour corresponds to the sinistral or dextral shell coil, or chirality, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Electrical stimulation of the right mesocerebrum evoked genital eversion and, in combination with tactile stimulation, dartshooting and penial eversion, suggesting that neurones of the right mesocerebrum play a pivotal role in controlling the mating behavior of C. aspersum (Koene et al, 2000). Moreover, lateralization of precopulatory mating behavior has been reported in the pond snail Lymnaea stagnalis (L.) (Pulmonata: Lymnaeidae), where the asymmetry of male circling behavior preceding mating corresponds to the sinistral or dextral shell coil, or chirality, of the snail, and it is apparently controlled by a maternal effect locus (Davinson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical stimulation of the right mesocerebrum evoked genital eversion and, in combination with tactile stimulation, dartshooting and penial eversion, suggesting that neurones of the right mesocerebrum play a pivotal role in controlling the mating behavior of C. aspersum (Koene et al, 2000). Moreover, lateralization of precopulatory mating behavior has been reported in the pond snail Lymnaea stagnalis (L.) (Pulmonata: Lymnaeidae), where the asymmetry of male circling behavior preceding mating corresponds to the sinistral or dextral shell coil, or chirality, of the snail, and it is apparently controlled by a maternal effect locus (Davinson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, lateralization of aggressive behavior has been investigated in few invertebrates (Frasnelli et al, 2012), mainly spiders (Ades and Ramires, 2002), fiddler crabs (Backwell et al, 2007), Mediterranean fruit flies (Benelli et al, 2015a), mosquitoes (Benelli et al, 2015b), blowflies (Romano et al, 2015), and honeybees (Rogers et al, 2013b). Also lateralization of courtship and mating behavior has rarely been investigated in invertebrates (Kamimura, 2006;Davinson et al, 2009), though some examples are available for vertebrates, including fish (e.g., Workman and Andrew, 1986;Cantalupo et al, 1996;Amcoff et al, 2009), amphibians (e.g., Green, 1977Giacoma, 2002, 2004), birds (e.g., Rogers et al, 1985;Ventolini et al, 2005;Templeton et al, 2014), and mammals (Bisazza et al, 1998a;Vallortigara and Rogers, 2005;Rogers et al, 2013a In this research, we investigated asymmetries of aggressive and courtship behavior in the olive fruit fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae), a worldwide pest of olive groves (Benelli et al, 2014a). B. oleae is a lekking species, forming aggregations in which males fight to defend a small territory (usually an olive leaf) where they court females and mate.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in snails (Lymnea stagnalis), the parietal and visceral ganglia are fused only on one side of the nervous system, leaving the contralateral visceral ganglion unpaired (figure 1h). The side of fusion corresponds to the chirality of the animal shell such as that in dextral individuals only the right parietal and visceral ganglia are fused [28]. Although further studies in snails are needed to determine a possible direct control of Nodal signalling on nervous system asymmetry, it has been shown that the chirality of the shell is dependent on the side of asymmetric Nodal expression [29,30].…”
Section: Nodal and Nervous System Asymmetry Across Metazoansmentioning
confidence: 99%
“…Brain lateralization, that was once considered a uniquely human characteristic, has been found and studied in a wide range of species, including nonhuman primates (e.g., Fernandez-Carriba, Loeches, Morcillo and Hopkins, 2002a,b;Forrester, Leavens, Quaresmini and Vallortigara, 2011), birds (e.g., Rogers, 1997;Rugani, Kelly, Szelest, Regolin and Vallortigara, 2010;Vallortigara, 2000), amphibians , fish (e.g., Andrew et al, 2009;Sovrano, Rainoldi, Bisazza and Vallortigara, 1999;Sovrano and Andrew, 2006) and invertebrates (e.g., Ades and Ramires, 2002;Byrne, Kuba and Griebel, 2002;Cooper, Nudo, González, Vinson and Liang, 2011;Davison et al, 2009;Frasnelli, Vallortigara and Rogers, 2010;Hobert, Johnston and Chang, 2002;Kigth, Steelman, Coffey, Lucente and Castillo, 2008;Letzkus, Boeddeker, Wood, Zhang and Srinivasan, 2007;Rogers and Vallortigara, 2008;Pascual, Huang, Nevue and Préat, 2004). Lateralization at the individual level (i.e., not necessarily characterized by a consistent bias within the population) is associated with clear computational advantages, such as the possibility to avoid a costly reduplication of functions and slow interhemispheric interactions, while allowing for more efficient parallel processing.…”
Section: Laterality In Social Recognitionmentioning
confidence: 99%